The Ability of Brand Image and Digital Promotion in Explaining Purchase Intention of Counterfeits Electronic Products - Kushariyadi Kushariyadi; Sukma Irdiana; Fahrina Mustafa; Sokid Sokid; Sugiarti Sugiarti (International Journal of Engineering, Science and Information Technology, 2025)
This study examines the effect of digital promotion and brand image on the intention to purchase counterfeit electrical devices. Since counterfeit goods are seeing a spike in the market, there is a fundamental need to build factors that encourage such buyers. A quantitative analytic approach will be used for this study. Data will be collected from 300 participants interested in buying counterfeit electronic products through an online survey. Most customers consider counterfeit goods viable alternatives to branded products, showing that consumers' perception of brands influences their buying habits considerably. Online advertisements also play a vital role, especially on social media, using e-commerce websites with alluring content to attract consumers. In addition, the study discovers that digital marketing and brand image are complementary; this means that people's perceptions about a brand's equity increase the effects of digital marketing campaigns. Digital platforms are generally utilized to advertise counterfeit products because of the status and affordability they display. Despite this, the study highlights the dangers and ethical issues associated with counterfeit products, regarding low quality and safety. These findings have significant regulatory and brand-related implications for the fight against counterfeiting and extend our knowledge of consumer behaviour generally. Therefore, we want to call for tighter regulations on counterfeiting and increase consumer education to reduce counterfeit products and boost ethical purchasing.